2016
DOI: 10.3847/0004-6256/152/5/140
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Gas Giant Planet in Microlensing Event Ogle-2014-BLG-1760

Abstract: We present the analysis of the planetary microlensing event OGLE-2014-BLG-1760, which shows a strong lightcurve signal due to the presence of a Jupiter mass ratio planet. One unusual feature of this event is that the source star is quite blue, with -=  V I 1.48 0.08. This is marginally consistent with a source star in the Galactic bulge, but it could possibly indicate a young source star on the far side of the disk. Assuming a bulge source, we perform a Bayesian analysis assuming a standard Galactic model, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(7 citation statements)
references
References 61 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…Penny et al (2016) suggested thepossibility of alack of planets in the Galactic bulge. OGLE-2013-BLG-1761Lb can be added to the growing list of planets discovered by microlensing, such as OGLE-2015-BLG-0051Lb (Han et al 2016a), OGLE-2014-BLG-1760Lb (Bhattacharya et al 2016), and OGLE-2012-BLG-0724Lb (Hirao et al 2016b), which counters this suggestion. This work contributes to thesample of planets found by microlensing, which is useful for testing planetary formation theories and the planet distribution in the Galaxy.…”
Section: Discussionmentioning
confidence: 94%
“…Penny et al (2016) suggested thepossibility of alack of planets in the Galactic bulge. OGLE-2013-BLG-1761Lb can be added to the growing list of planets discovered by microlensing, such as OGLE-2015-BLG-0051Lb (Han et al 2016a), OGLE-2014-BLG-1760Lb (Bhattacharya et al 2016), and OGLE-2012-BLG-0724Lb (Hirao et al 2016b), which counters this suggestion. This work contributes to thesample of planets found by microlensing, which is useful for testing planetary formation theories and the planet distribution in the Galaxy.…”
Section: Discussionmentioning
confidence: 94%
“…However, the value of the lens-source proper motion, 6.0±1.2 mas yr −1 , does not rule out a scenario with a lens and source lying in the Galactic bulge (Koz lowski et al 2006). If it is confirmed that the new exoplanetary system OGLE-2015-BLG-1670L lies in the Galactic bulge, then it will be one more object in the growing list of planets orbiting stars in the bulge, similar to MOA-2011-BLG-293Lb (Yee et al 2012;Batista et al 2014), OGLE-2015-BLG-0051Lb (Han et al 2016), OGLE-2014-BLG-1760Lb (Bhattacharya et al 2016), OGLE-2012-BLG-0724Lb (Hirao et al 2016), and OGLE-2013-BLG-1761Lb (Hirao et al 2017). In the future, it will be possible to use this sample to assess the planet demography close to the Galactic center and test whether or not there is a lack of planets in the Galactic bulge (Penny et al 2016).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…There are several ingredients to this improvement. The improved MOA and CTIO photometry provides more accurate t E and color values, and the analysis of Boyajian et al (2014), as optimized for microlensing targets (Bhattacharya et al 2016), provides a more accurate source radius. Finally, Nataf et al (2013) has provided a more accurate determination of the properties of the red clump giants that are used to determine the dust extinction in the foreground of the source.…”
Section: Revisiting Photometry and Light-curve Modelingmentioning
confidence: 99%
“…which comes from the Boyajian et al (2014) analysis, but with the color range optimized for the needs of microlensing surveys (Bhattacharya et al 2016).…”
Section: Lens Propertiesmentioning
confidence: 99%